O-GlcNAcylation dictates pyroptosis - Lang, Yue; Li, Jincheng; Zhang, Leiliang (Frontiers in Immunology, 2024)
O-GlcNAcylation is a dynamic post-translational modification involving the attachment of N-acetylglucosamine to serine and threonine residues. This review emphasizes its role in regulating the signaling pathways of pyroptosis. Specifically, the O-GlcNAcylation of GSDMD is linked to the modulation of pyroptosis, suggesting that enhancing O-GlcNAcylation of GSDMD could be crucial for improving hypoperfusion in sepsis. Additionally, GSDME, another member of the gasdermin family, facilitates macrophage pyroptosis through O-GlcNAcylation induced by high glucose levels in the context of periodontitis. The review also examines the effects of O-GlcNAcylation on the NLRP3 inflammasome and its regulators, including NEK7 and NF-κB. Overall, this review emphasizes the role of O-GlcNAcylation in the pathogenesis of conditions such as sepsis, periodontitis, and osteoarthritis, identifying potential therapeutic targets for managing inflammatory responses through its targeted modulation.